Agronomic performance of mung bean (Vigna radiata) with the application of extracts from Clausena anisata, Clutia abyssinica, and Lobelia giberroa under field conditions - Kessy, Godfrey Adolph; Mkindi, Angela Gerald; Binagwa, Papias Hongera; Ndakidemi, Patrick Alois (Frontiers in Sustainable Food Systems, 2024)
This study investigated the effects of four plant extracts on the agronomic performance of mung bean (Vigna radiata) during the 2020 growing season at two sites in the northern highlands of Tanzania, namely Miwaleni and TARI Selian, located in the Kilimanjaro and Arusha regions, respectively. The extracts tested included Tephrosia vogelii, Clutia abyssinica, Clausena anisata, and Lobelia giberroa, using a randomized complete block design with four replications. Extract concentrations ranged from 0 to 10,000 mg, with the mung bean variety “Imara” being used. The results indicated that the Miwaleni site significantly outperformed SARI Selian in grain yield, with 762 and 279 kg ha−1, and plant height, with 59.6 and 58.6 cm, respectively. Notably, L. gibelloa produced the highest grain yield at 583.6 kg ha−1, significantly (p = 0.011) greater than that of C. anisata (434.7 kg ha−1). Yields from T. vogelii (542.8 kg ha−1) and C. abyssinica (521.6 kg ha−1) were not significantly different from L. gibelloa. For plant height, C. abyssinica and L. gibelloa had the tallest averages at 60.1 and 60.3 cm, respectively, although these differences were not statistically significant. The interaction between extract concentrations and their effects on yield and height was also examined. At 0% concentration, L. gibelloa had the highest yield (648.8 kg ha−1) and height (65 cm). A concentration of 100 mg generally improved yields for the majority of extracts, particularly C. abyssinica (569.8 kg ha−1), while higher concentrations (1,000 and 10,000 mg) led to significant reductions in yield and height, especially for C. anisata. These findings highlight the importance of optimizing extract levels and considering site-specific factors for enhancing mung bean productivity and sustainability, emphasizing the potential of L. gibelloa in improving yields.